2007
DOI: 10.1002/app.26177
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight polypropylene nanospheres: Synthesis and characterization

Abstract: The high molecular weight (MW) polypropylene with average particle size of 60 nm was synthesized by controlled growth mechanism using ZieglerNatta catalyst. The atomic force microscopy (AFM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) studies showed that PP nanoparticles were spherical in shape. Structure and crystallinity were concomitantly studied through Fourier transform infrared spectroscopy and X-ray diffraction, respectively. It shows nanospherical PP particles with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Due to higher compactness of chains, it takes much more time to attain the thermal equilibrium as well as degradation process occurred slowly. Additionally, these results may be attributed to the smaller particle size, which may have different surface morphology, surface roughness, crystal structure and higher crystallinity for PP nanoparticles compared with the microsized particles [24]. In this circumstance it is important to mention that the purity of PP macro-, micro-and nanoparticles is same and confirmed by FTIR spectroscopy (figure not shown here).…”
Section: Thermogravimetry (Tg) and Differential Thermogravimetry (Dtgmentioning
confidence: 79%
“…Due to higher compactness of chains, it takes much more time to attain the thermal equilibrium as well as degradation process occurred slowly. Additionally, these results may be attributed to the smaller particle size, which may have different surface morphology, surface roughness, crystal structure and higher crystallinity for PP nanoparticles compared with the microsized particles [24]. In this circumstance it is important to mention that the purity of PP macro-, micro-and nanoparticles is same and confirmed by FTIR spectroscopy (figure not shown here).…”
Section: Thermogravimetry (Tg) and Differential Thermogravimetry (Dtgmentioning
confidence: 79%
“…The PP nano and micro particles with high molecular weight were synthesized using the method as discussed in our previous work and the chemical structure was studied through FTIR [18][19][20]. The morphology, particle size and its distribution were studied through SEM, TEM and AFM.…”
Section: Resultsmentioning
confidence: 99%
“…The authors would like to mention that though the particle size is in nanometer scale but the molecular weight of this nano sized PP is equal to the commercially available PP. The synthesis method has been discussed in detail by the authors [18][19][20].…”
Section: Synthesis Of Pp Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…, esistance especially at low temperature considerably limits its application [1,2] . Therefore, numerous studies have been reported concerning the reinforcement of PP using different types of inorganic minerals in order to achieve improvement in many aspects [3] . These include increase of modulus and , , strength improved barrier properties increase in sol-, vent and heat resistance good optical transparency and , reducing the production cost of molded products etc.…”
mentioning
confidence: 99%